2017
DOI: 10.1308/rcsann.2016.0324
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury following primary hip and knee arthroplasty surgery

Abstract: Acute kidney injury (AKI) is a recognised postoperative complication following primary hip/knee arthroplasty surgery. The aim of this study was to determine causative and potentially modifiable risk factors associated with postoperative AKI. Standard data were collected for 413 consecutive arthroplasty patients, both retrospectively and prospectively. Univariate and multivariate analyses were performed to identify any potential causative factors. Eight percent of patients developed postoperative AKI. Univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 28 publications
2
35
2
2
Order By: Relevance
“…In this study, of those subjects who had their postoperative sCr measured, 2.9% fulfilled the AKI criteria. This is in agreement with previous reports, where the incidence of AKI varies between 2% and 15% among patients undergoing lower limb arthroplasty …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, of those subjects who had their postoperative sCr measured, 2.9% fulfilled the AKI criteria. This is in agreement with previous reports, where the incidence of AKI varies between 2% and 15% among patients undergoing lower limb arthroplasty …”
Section: Discussionsupporting
confidence: 94%
“…The most common indications for these operations are osteoarthosis, rheumatoid arthritis and traumatic fractures . Several previous studies have examined the risk factors for AKI and reported its incidence to vary between 2% and 15% among patients undergoing lower limb arthroplasty . In these studies, no age‐related exclusion criteria were used, only elective arthroplasties were examined, or only patients with normal preoperative kidney function were included …”
Section: Introductionmentioning
confidence: 99%
“…Dubrovskaya et al 20 and Ferguson et al, 26 in contrast, found no increased risk with addition of gentamicin.…”
Section: Aminoglycoside Use As a Risk Factormentioning
confidence: 93%
“…Multiple studies assessed the risk of acute kidney injury comparing regimens containing an aminoglycoside (typically gentamicin) with regimens lacking these agents. [20][21][22][23][24][25][26] In general, these studies found a signifi cantly higher risk of acute kidney injury when gentamicin was used.…”
Section: Aminoglycoside Use As a Risk Factormentioning
confidence: 97%
See 1 more Smart Citation